Teacher’s Feedback on Students’ Writing - Diah Nisfu Faroha; Asnawi Muslem; Dian Fajrina (Universitas Syiah Kuala, 2016)
The objectives of this study were to find out the kinds of written feedback and the reasons for using those feedbacks on students’ writing by English teachers of SMA Negeri 11 Banda Aceh. This research used descriptive qualitative method and the data were collected through documentation and interview. The framework undertaken is proposed by Harmer (2007) and the interview question was adapted from Thorsteinsen (2010). The findings found that there were two kinds of feedbacks namely, direct written feedback and indirect written feedback. Eighty-four direct feedbacks were found which consisted of 70 direct answers and 14 responding by written comments. Meanwhile, 49 indirect written feedbacks consisted of six coded and 43 un-coded feedbacks. In conclusion, teachers’ written feedbacks are important to make students aware of making mistake on writing task. The findings suggested that English teachers should give written feedback to students’ writing task to enable them to improve the skill.